Peritalar osteotomy for rigid pes cavus and cavovarus - Michael S Pinzur; Ryan LeDuc; Adam P Schiff; Kamran Hamid (Journal of Limb Lengthening & Reconstruction, 2023)
Level of Evidence: IV retrospective case review. Background: Patients with rigid pes cavus and pes cavovarus deformities can present with a challenging multiplanar rigid bony deformity that impairs walking stability. Corrective osteotomies or triple arthrodesis are very difficult to both perform and maintain with standard methods of internal fixation. Methods: A retrospective chart review identified 17 patients (20 feet) who underwent peritalar osteotomy and maintenance of the correction with a "miter" frame circular external fixator construct. There were 15 males and 2 females (three underwent sequential bilateral surgery). The average age at the time of surgery was 47.6 years. Four of the 17 patients (one bilateral) were insulin-requiring diabetics. Follow-up averaged 58.3 months. One diabetic patient with multiple organ system disease developed a postoperative wound infection that required formal surgical debridement. He died of unrelated causes before the removal of the external fixator. A second postoperative wound infection was managed with local wound care. One pin-tract infection required late debridement following removal of the external fixator. Results: Sixteen of the 20 feet achieved the surgical goal of walking with standard oxford footwear. Three patients required short ankle–foot orthoses but were unrestricted community ambulators. Conclusions: It is very difficult to both obtain and maintain a stable plantigrade foot when attempting surgical reconstruction for rigid pes cavus or pes cavovarus deformities. Preliminary experience with a peritalar osteotomy, acute correction of the multiplanar deformity, and maintenance with a "miter" frame circular external fixator suggest a more predictable clinical outcome compared with historic methods of treatment.